2015
DOI: 10.1021/acs.est.5b02873
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Activity Framework for Assessing Aquatic Ecotoxicology Data for Organic Chemicals

Abstract: Toxicological research in the 1930s gave the first indications of the link between narcotic toxicity and the chemical activity of organic chemicals. More recently, chemical activity has been proposed as a novel exposure parameter that describes the fraction of saturation and that quantifies the potential for partitioning and diffusive uptake. In the present study, more than 2000 acute and chronic algal, aquatic invertebrates and fish toxicity data, as well as water solubility and melting point values, were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…A lower critical target lipid body burden for this 7‐d test is also consistent with lower critical target lipid body burden distribution derived from soil and sediment toxicity datasets that typically involve longer (7–28‐d) exposure durations than standard 48‐h to 96‐h acute tests . Expression of toxicity endpoints in terms of chemical activity for both species indicated EC50s in the range of approximately 0.01 to 0.1 (Tables and ), consistent with the range reported for baseline toxicity .…”
Section: Resultssupporting
confidence: 82%
“…A lower critical target lipid body burden for this 7‐d test is also consistent with lower critical target lipid body burden distribution derived from soil and sediment toxicity datasets that typically involve longer (7–28‐d) exposure durations than standard 48‐h to 96‐h acute tests . Expression of toxicity endpoints in terms of chemical activity for both species indicated EC50s in the range of approximately 0.01 to 0.1 (Tables and ), consistent with the range reported for baseline toxicity .…”
Section: Resultssupporting
confidence: 82%
“…It is therefore unsurprising that the 2 regression lines for acute and chronic data are parallel for baseline narcotics (MechoA 1.1). In reality, the toxicities for acute data (fish, daphnids, and algae) do not occur at a constant activity but are observed to fall at an activity between 0.1 (i.e., at −1 log unit below the solubility cutoff) and 0.01 (i.e., at −2 log units below the solubility cutoff) as observed by several authors (Mackay et al ; Schmidt and Mayer ; Thomas et al ), for over 5 log units of solubility (i.e., the regression slope is approximately 0.8, rather than 1 as proposed by Mackay et al []). This observation can be seen for the results presented on daphnid toxicity in Figures A and B.…”
Section: How Can Qsars Increase Confidence In Acute To Chronic Ratiosmentioning
confidence: 62%
“…The authors consider this descriptor more appropriate than the more classically used log K OW (octanol–water partitioning coefficient) because the fugacity of the substance in water and in the organisms at steady state is directly related to the chemical activity of the substance, and the chemical activity is a direct function of its (subcooled liquid) water solubility. The subcooled aspect is only critically important for solids (Ferguson ; Bobra et al ; Mackay et al ; Thomas et al ). When plotting the logarithm of the toxicity (as E/LC50 in mol/L) versus the logarithm of the subcooled liquid solubility (in mol/L), the regression can be experimentally demonstrated to hold true over several orders of magnitude of solubility between a log solubility of approximately −4 to −5 (depending on the species) at the hydrophobic end and 0 at the hydrophilic end.…”
Section: How Can In Silico Approaches Be Used To Predict Values When mentioning
confidence: 99%
“…Several authors have shown that many individual chemicals exert a baseline toxicity that is closely related to the chemical activity of the chemical in organisms. For example, several authors have shown that many individual neutral organic chemicals cause lethality in organisms when they reach chemical activities between 0.01 and 0.1 (Reichenberg and Mayer ; Schmidt et al ; Thomas et al ). Mixtures of these chemicals appear to cause the same biological response as the individual chemicals when the combined chemical activity in the organism, determined as the sum of the chemical activities of the mixture's components, reaches critical values similar to those of the individual components of the mixture (Schmidt et al ; Smith et al ).…”
Section: Theorymentioning
confidence: 99%